The "vintage fashion" view from the chronotopic concept (ModaPalavra e-periódico, 2015)
This paper aims to analyze the concept of vintage applied to fashion, by the chronotope concept of Mikhail Bakhtin's that for applicability of reasons, has been reviewed by Anthony Wall. The primary idea of this concept within the philosophy, reported in the writings of Bakhtin, refers to the indissolubility of time and space in the literature, while Wall, to relate the spatialand temporal relations to memory, gives greater scope to understanding chronotopic by including it in a social sphere. Based on these ideas, we sought to analyze the reasons why the postmodern subject reproduces the past through the reutilization of original robes, which characterizes the definition of "vintage fashion" expression. By linking this practice to memory and identity, it became possible to observe that the reappropriation of old clothes is the very objectification of chronotopic concept in contemporary fashion.
Keywords: chronotope; vintage; fashion